Study of an Authentication Methods for IoT Services - Lee, Aeri; ., . (International Journal of Engineering and Technology, 2018)
The Internet of Things refers to an intelligent technology and service in which information is mutually communicated between men and things and between things by connecting all things based on the Internet. Recently, as the connections accelerate among heterogeneous terminals, networks, and applications through the opening of IoT platforms, many technical and managerial security threats occur in the IoT environment. To deliver information accurately and securely in the IoT environment, it is getting very important to solve the problems of the safe authentication system. This study proposes an efficient authentication method for IoT services and analyzes its safety.Â Â